Strategi Peningkatan Pelayanan Pengujian Kendaraan Bermotor Dalam Upaya Meningkatkan Pendapatan Asli Daerah Pada Dinas Perhubungan Kabupaten Ciamis - Mubarrok, Dede Husni; Mahara, Mualif Ibnu; Amin, Tsalis Rahman; Lestari, Vina Resti; Mubarok, Zaki; Nurliani, Rika (Khidmat, 2022)
This article on community service seeks to investigate the service method employed by the Motor Vehicle Testing UPTD of the Ciamis Transportation Service to enhance local revenue by means of levies on motor vehicle testing. The Motor Vehicle Testing Levy is a primary source of revenue for Ciamis Regency. This tax plays a significant role in contributing to the Original Regional Income of Ciamis Regency. The administration of the Motor Vehicle Testing Levy is overseen by the Ciamis Regency Transportation Service. This study employs descriptive research methodologies with a qualitative approach. Explore research methodologies involving the utilization of observation, interviews, and document analysis for data collection. Following the provision of help and service, there are 9 ways that can be employed to enhance the local revenue at the Ciamis Regency Transportation Service.